Implementación de la sucursal del centro comercial su economía en el Cantón La Maná, y su impacto socio-económico en los consumidores. - Calvo Fuentes, Sandra Vanessa (2017)
The present research project had as general objective to realize a business plan for the implementation of a branch of the Stores “Su Economía” in La Maná and Copaxi to measure its socioeconomic impact on its consumers. The idea of the proposal was born in the face of the problem lack of places where consumers can make their purchases with comfort and competitive prices. For the development of the proposal, it was used the bibliographic research that allowed to gather information for the development of the scientific basis, the descriptive research for the presentation of the results and the field research for obtaining information through an interview with the owner and surveys directed to the population of in La Maná. The results of the market study reflected a demand of 23,984,135 and an offer of 16,788,985 giving unsatisfied demand of 7,195,241 units of rice, Coca Cola, milk, egg and toothpaste, establishing the existence of a large market to capture . In the technical study, 5% of the unsatisfied demand according to the availability of financing, labor and infrastructure was defined as the size of the project. In addition, the description of the supply, storage and sale of consumer products was established through flow charts. In addition, the technical study describes the organizational, legal and organizational requirements. The results of the economic study revealed that an initial investment of $ 203,528.62 was required, which was financed through 90% equity and 10% with a financial loan, earning a profit of $ 168.262,54 for the first year and VAN de $391.320,59 and a TIR of 22% during the 5 years of research project. The measurement of social and economic development was very significant due to the creation of new jobs, greater dynamism in the area and improved competitiveness in the sale of consumer products therefore it was established that the proposal is viable.